2013
DOI: 10.1039/c3tc30763h
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensor based on the UV upconversion luminescence of Gd3+ in Yb3+–Tm3+–Gd3+ codoped NaLuF4 microcrystals

Abstract: Optical temperature sensing characteristics based on the ultraviolet (UV) upconversion luminescence (UCL) of Gd 3+ ions are reported here for the first time. Under 980 nm excitation, the temperature dependence five-photon UV UCL from the 6 P J and 6 I J levels of Gd 3+ ions in NaLuF 4 :Yb 3+ , Tm 3+ , Gd 3+ microcrystals were investigated systematically. The fluorescence intensity ratios (FIR) of two pairs of thermally coupled levels ( 6 P 5/2 , 6 P 7/2 and 6 I 9/2 , 6 I 7/2 ) were studied as a function of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(76 citation statements)
references
References 29 publications
0
75
1
Order By: Relevance
“…[1][2][3][4][5][6]. The optical temperature sensing, based on the UC emission of RE ions, by means of the fluorescence intensity ratio (FIR) technique has received significant attention as a result of its high sensitivity and accuracy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6]. The optical temperature sensing, based on the UC emission of RE ions, by means of the fluorescence intensity ratio (FIR) technique has received significant attention as a result of its high sensitivity and accuracy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Optical thermometry used a line shift technique was first reported in Y 2 O 2 S:Eu phosphor by Kusama et al [1]. From then on, optical temperature sensing was widely studied in the CdSe and CdTe semiconducting quantum dots, organic phosphors, rare earth ion-doped oxide bulks, fluoride nanoparticles, and glass ceramics containing fluoride nanocrystals [2][3][4][5][6][7][8][9]. Among the materials used for optical thermometry, quantum dots nano-crystals, fluoride nano-crystals, and organic compounds are easy to be oxidized at high temperature, and only available in low-temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…The k is the Boltzmann constant and T is absolute temperature. There are many reports on temperature sensing behavior of rare earth ions doped materials and authors have reported improved sensitivity of the phosphors [22,32,37]. It is well known that emission wavelengths of rare earth ions are very less sensitive to the environment, so question is which factors increase the sensitivity of the samples.…”
Section: Temperature Sensing Behavior Of Nano-composite Phosphormentioning
confidence: 98%